LAND USE AND LAND COVER CHANGES IN A HUMAN-WILDLIFE MEDIATED LANDSCAPE OF SAVE VALLEY CONSERVANCY, SOUTH-EASTERN LOWVELD OF ZIMBABWE - C. Mashapa; E. Gandiwa; N. Muboko; P. Mhuriro-Mashapa (Journal of Animal and Plant Sciences, 2020)
The study aimed to map and predict land use and land cover change dynamics in a human-wildlife mediated landscape of Save Valley Conservancy (SVC), south-eastern lowveld of Zimbabwe. In April 2018, remote sensing was used to quantify land use and land cover changes between 1990 and 2015 based on satellite images acquired from North Atlantic Space Agency (LANDSAT TM, path 170 raw 73). Household surveys were administered using a structured questionnaire to 100 communal settlers to collect biophysical/socioecological data on explanatory variables which included; density of human and livestock, fuelwood consumption and area under cultivation. The study used multi-criteria evaluation procedure based on dynamic adjustments of socio-ecological data to generate transitional probability maps of SVC. Thresholds of socio-ecological data were then computed in the Markov-cellular automata model through a multi-objective land allocation procedure and a cellular automata spatial filter in order to simulate future land use and land cover maps of 2020, 2030 and 2040 for SVC. If the Zimbabwe land reform and its agricultural resettlement program is not properly coordinated and planned in the study area, the study predicted a continuing downward trend in woodland cover category and a significant upward trend of land under agriculture. For the period 1990 to the 2040s, the woodland cover is likely to decrease by 46.7% changing into agricultural land use and/or bare land in SVC. Future land use and land cover simulations indicated that if the current land use and land cover trends continue unabated across the study area without a holistic sustainable agricultural land-wildlife management plan and community development measures, severe woodland degradation will occur. The study recommends ecological restoration and/or re-planning on agriculture-wildlife land use and zonation, delineating agriculture and human settlement in the southern part of the conservancy while the northern part of SVC is exclusively reserved and protected for wildlife management.
Keywords: Land use; land cover; human encroachment; protected area; savanna